The study of ( Columba livia domestica) Pigeon as bioindicator of contamination with zinc, lead and cadmium in Khartoum state - Gassim, Tawassul Mahadi (Journal of Faculty of Education, 2021)
The objective of the study is to provide evidence that pigeon is a good bioindicator of environmental pollution with Pb and Cd as heavy metals and Zn as trace element. Ninty samples of Columba livia were collected from rural, urban and industrial areas in Khartoum State. The birds were killed and metal concentrations were tested with atomic absorption spectrophotometer after treated by wet ash procedures. The results divided serum and target tissues according to richest with metals in thes order: serum> liver> kidney> feather and the three metals Cd> Pb> Cd respectively. The study showed that industrial areas are the richness area with Zn, Pb and Cd and considers feathers as the best monitor of air pollution in the study area.